Investigating the anticancer efficacy of biogenic synthesized MgONPs: An in vitro analysis - Shams Tabrez; Shams Tabrez; Azhar U. Khan; Mehboob Hoque; Mohd Suhail; Mohd Suhail; Mohammad Imran Khan; Torki A. Zughaibi; Torki A. Zughaibi (Frontiers in Chemistry, 2022)
The biogenic approach of synthesizing metal nanoparticles is an exciting and interesting research area with a wide range of applications. The present study reports a simple, convenient, low-cost method for synthesizing magnesium oxide nanoparticles (MgONPs) from pumpkin seed extracts and their anticancer efficacy against ovarian teratocarcinoma cell line (PA-1). The characteristic features of biogenic MgONPs were assessed by UV–visible spectrophotometry (UV–vis), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The formation of spherical NPs with an average size of 100 nm was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Moreover, MgONPs exhibit considerable cytotoxicity with an IC50 dose of 12.5 μg/ml. A dose-dependent rise in the induction of apoptosis, ROS formation, and inhibition in the migration of PA-1 cells was observed up to 15 μg/ml concentration, reflecting their significant anticancer potential against ovarian teratocarcinoma cell line. However, additional work, especially in different in vitro and in vivo models, is recommended to find out their real potential before this environment-friendly and cost-effective nanoformulation could be exploited for the benefit of humankind.